The false traitor, Louis Riel in Canadian literature - Braz, Albert Raimundo (1999)
grantor: University of Toronto The nineteenth-century Métis leader Louis Riel has emerged as one of the most popular—and elusive—figures in Canadian culture. Since his hanging for treason in 1885, the self-declared David of the New World has been depicted by Canadian novelists, poets, and playwrights variously as a traitor to Confederation; a French-Canadian and Catholic martyr; a bloodthirsty rebel; a pan-American liberator; a pawn of shadowy white forces; a Prairie political maverick; a First Nations hero; an alienated intellectual; a victim of Western industrial progress; and even a Father of Confederation. The primary objective of this thesis is to investigate how a historical figure, someone who supposedly existed in space and time, could be portrayed in such contradictory ways. Especially in light of the fact that most aesthetic representations of Riel bear little resemblance not only to one another but also to their ostensible model, it is suggested that those works are only nominally about the Métis leader himself. That is, they reveal less about the politician-mystic than they do about their authors and the society to which they belong. Ph.D.